Isolasi bakteri probiotik dari organ pencernaan ikan mas (Cyprinus carpio) - Bella, Sintia S. (e-Journal BUDIDAYA PERAIRAN, 2018)
The study aimed to isolate probiotic bacteria from the digestive organs of goldfish taken from Fish Hatchery, Tateli. As much as 1 g of the intestine was crushed, put in 9 mL NaCl and centrifuged twice at 1000 rpm for 10 minutes. The supernatant was removed and diluted at a concentration of 10-2 - 10-3, then spread on the surface of the MRS media. The bacteria were incubated at 280C for 24-48 hours in the Incubator. The Gram Stain test found that the isolated bacterium was gram positive, biochemical tests found that bacterium isolated from the gut of carp was Lactobacillus sp. while pathogenicity test found that there was no mortality of fish until the 14th day after the challenge test. So that it could be concluded that the bacteria obtained could be used as probiotics.Keywords: probiotic, Lactobacillus sp., Gram Stain, pathogenesity